2005
DOI: 10.1007/s00392-005-0301-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of NT-pro-BNP in patients with atrial fibrillation before and after electrical cardioversion

Abstract: Atrial fibrillation in patients with a normal left ventricular ejection fraction is associated with elevated NT-pro-BNP plasma levels, which decrease when a persistent sinus-rhythm can be restored by electrical cardioversion. On the other hand, NT-pro-BNP seems to increase (n.s.) when recurrence of atrial fibrillation occurs. Finally, NT-pro-BNP is no valid predictor for long-term success of sinus-rhythm restoration by electrical cardioversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 24 publications
4
35
1
1
Order By: Relevance
“…Atrial fibrillation increases the plasma NT-proBNP by approximately 50% [12,13], although we found no statistically significant influence on the correlations. This is probably because atrial fibrillation does not alter the relationship between NTproBNP in plasma and urine.…”
Section: Previous Studiescontrasting
confidence: 75%
“…Atrial fibrillation increases the plasma NT-proBNP by approximately 50% [12,13], although we found no statistically significant influence on the correlations. This is probably because atrial fibrillation does not alter the relationship between NTproBNP in plasma and urine.…”
Section: Previous Studiescontrasting
confidence: 75%
“…These biomarkers help to diagnose and manage patients with HF, but their role in atrial fibrillation (AF) is still not established. In several studies, it was shown that the mean level of NT-proBNP in AF ranged between 800 pg/mL and 1100 pg/mL [3].…”
Section: Introductionmentioning
confidence: 99%
“…The association between NT-pro-BNP level and atrial fibrillation has been less studied and understood. Some studies have proved that NT-pro-BNP is increased in atrial fibrillation [16][17][18][19]. The proposed mechanisms are high frequency of atrial myocyte contraction and local atrial inflammation [18].…”
Section: Discussionmentioning
confidence: 99%